PENGARUH GAYA KEPEMIMPINAN, MOTIVASI, DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN DI UNIVERISTAS WINAYA MUKTI BANDUNG - Fatkar, Budiastuti; Melani, Rike (Universitas Islam Syekh-Yusuf, 2019)
The main problem in this research is how big influence leadership style,motivation, andorganization culture againts employee perfomance (A study on theWinaya Mukti Bandung University), either simultaneously or partially.Interest to undertake this work is to invetigate and analyze theleadershipstyle, motivation, organization culture and employee peformance as well asthe influence of leadership style, motivation and organization culture on employeeperformance at the Winaya Mukti Bandung University, either simultaneously orpartially.The method used in this research is descriptive and verification approaches.The population in this study are employees of the Winaya Mukti BandungUniversity with a sample 50 people, the data in this study were obtained from therespondents answers to a questionnaire author spreads.Keywords : leadership style, motivation, organizational culture,employeeperformance